Modeling decisions for artificial intelligence : 12th International Conference, MDAI 2015, Skövde, Sweden, September 21-23, 2015, Proceedings /: 12th International Conference, MDAI 2015, Skövde, Sweden, September 21-23, 2015, Proceedings. (2015) - Unknown
No abstract available